Analisa Hubungan Situasi Komunikasi Organisasi dengan Kepuasan Kerja para Guru MI Al-Hidayah II Bandarlor Kecamatan Mojoroto Kota Kediri - Siti Khotijah; Siti Wahyuni (Indonesian Journal of Humanities and Social Sciences, 2020)
The creation of good communication relationships in the school environment which is reflected in the atmosphere of a harmonious and conductive relationship between school principals, teachers and school employees. The goal is to facilitate the achievement of educational goals. The research method used in this research is descriptive quantitative method. The population in this study amounted to 18 people using the data collection technique is a questionnaire. The results of data analysis and statistical calculations using the help of the SPSS 22 program regarding the relationship of organizational communication with job satisfaction, it can be concluded that there is a significant relationship between organizational communication and job satisfaction at MI Al Hidayah II Bandar Lor, Kediri City. This can be seen from the size of r count = 0.684 which is greater than r table = 0.468. In addition, it can also be shown by the value of Fcount = 14.030 which is greater than Ftable = 2.021. The relationship between organizational communication and job satisfaction at MI Al Hidayah II Bandar Lor Kota Kediri is 46.7%, and the remaining 53.3% is caused by other factors which are not the focus of discussion in this study.